Computed tomography liver volumetry in living donor liver transplantation: influence of the slice thickness on the volume calculation - Tooba Fatima; Muhammad Salman Rafique; Sana Kundi; Tahir Malik; Faryal Ijaz; Sahar Zulfiqar (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effect of slice thickness on multidetector computed tomography-based preoperative liver volumetry, and to compare the time consumed during volumetry between thin and thick slices. Method: The retrospective study was conducted at the Pakistan Kidney and Liver Institute and Research Centre, Lahore, Pakistan, and comprised data from September 2022 to January 2023 of patients who underwent donor hepatectomy. Liver volumetry was done on thick 5mm and thin 0.625mm slices, and the consumed time was calculated. The calculated volumes were then compared to the actual per-operative graft volume. Data was analysed using SPSS 20. Results: Of the 30 donors, 20(66.7%) were males and 10(33.3%) were females. The overall mean age was 26 years (range: 19-44 years, SD=6.25). The mean estimated graft volume on thick slices was 668.57±169.83g compared to 693.70±174.78g on thin slices (p>0.05). The time taken to calculate estimated graft volume on thick slices was 7.29±0.97 minutes compared to 44.07±4.78 minutes on thin slices (p<0.05). The mean actual per-operative graft volume was 632.40±160.03. Conclusion: There was no significant difference between the volumes calculated on thick and thin slices, but there was significant difference in time taken for volumetry.